TikTok Addiction and Academic Stress Among University Students: Examining the Mediating Role of Social Support - Aditomo, Imam Riefly; Swastika, Amalia Fasha Nur; Imanda, Erlisa Nur Diana (International Journal Administration, Business & Organization, 2025)
This study investigates the interrelationship between TikTok addiction, perceived social support, and academic stress among university students in Surakarta. Grounded in the stress-buffering framework, the research explores the direct and indirect effects of compulsive TikTok use on academic stress, with social support examined as a mediating variable. A cross-sectional design was employed, using purposive sampling to collect data from 452 TikTok users enrolled in higher education. TikTok addiction, social support, and academic stress were measured using adapted and validated scales. Structural equation modelling with SmartPLS revealed that TikTok addiction significantly increases academic stress, while social support reduces it. Interestingly, TikTok use was positively associated with perceived social support, though its mediating role in buffering academic stress was limited. The findings underscore the complex psychosocial dynamics of digital behavior and suggest that enhancing social support systems may help mitigate the academic strain associated with social media overuse.